2016
DOI: 10.1063/1.4954078
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage culture process using Chlorella vulgaris for urban wastewater nutrient removal and enhanced algal lipid accumulation under photoautotrophic and mixotrophic conditions

Abstract: Microalgae such as Chlorella vulgaris contain sufficient fatty acids to suggest their use as feedstocks for biodiesel production. Their capacity to remove nitrogen, phosphate, and other nutrients from a culture medium makes them a potentially useful element in urban wastewater treatment systems. A two-stage process was used to grow Chlorella vulgaris under mixotrophic and autotrophic conditions in artificial wastewater and urban wastewater media. Growth rate, nutrient removal, and lipids accumulation were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The transesterification of fatty acids was according to the methods by Sato and Murata [14]; and Canedo-Lopez et al [5]. The FAMEs profiles were generated with a Gas Chromatographer (GC) (Agilent Technology 7890).…”
Section: Fatty Acid Extraction and Composition Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The transesterification of fatty acids was according to the methods by Sato and Murata [14]; and Canedo-Lopez et al [5]. The FAMEs profiles were generated with a Gas Chromatographer (GC) (Agilent Technology 7890).…”
Section: Fatty Acid Extraction and Composition Analysismentioning
confidence: 99%
“…Producing sufficient biomass with enhanced lipids contents can be done using a two-stage culture strategy [4]. In this strategy, an alga is first grown under nutrientsufficient conditions to allow maximum cell density, and then deprived of certain nutrients to trigger lipids accumulation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of various forms of nitrogen and phosphorous in wastewater leads to eutrophication [38]. C. vulgaris has a high potential to reduce nutrients in secondary waste water treatment plants effluents [39] [40] [41] while simultaneously producing algal biomass with sufficient lipids content and an acceptable fatty acids profile for use as a biodiesel feedstock [42].…”
Section: Resultsmentioning
confidence: 99%
“…While there are many studies available on microalgae about nutrient removal from wastewater used in indoor PBRs in literature, limited studies on outdoor PBRs have been found. TN and TP removal were found maximum up to 90% and 100%, respectively, in indoor PBRs [20,29,30]. Several studies claim that algal systems integrated with different types of wastewater, i.e., brewery wastewater, swine wastewater, municipal wastewater, etc., 90-100% BOD, 60-99.9% COD, 99.96% TP, 100% total carbon and 40-90% ammonium nitrogen [31][32][33].…”
Section: Bioremediation Efficiencymentioning
confidence: 99%